The Prevalence of Radiographic Signs of Pincer Type Morphology in a Population Based Cohort Study of Asymptomatic Japanese. Issue 4 (25th July 2016) - Mochizuki, Yoshihito; Kokubo, Yoshiyasu; Yamazaki, Takashi
Background: This study was designed to document the prevalence of radiographic findings of pincer-type morphology in an asymptomatic population and determine any relationship to age. Methods: A total of 2, 104 hips in 1, 052 patients (mean age 38.9 years [10-59]), who underwent abdominal/pelvic computed tomography for other conditions, were identified retrospectively. Anteroposterior scout radiographs were used to detect the acetabular crossover sign (COS), prominent ischial spine (PRIS), coxa profunda (CP), and posterior wall sign (PWS). Subgroup analyses of signs were performed by age (group 1: 532 hips in <30-year-old patients; group 2: 1, 572 hips in ≥30-year-old patients). Results: COS and PRIS was observed significantly more often in group 1 vs. group 2: COS was 73.1% vs. 29.3% in group 2, p<0.001; PRIS was 23.9% vs.7.4% in group 2, p<0.001. CP and PWS was observed significantly less frequently in group 1 vs. group 2: CP 3.4% vs. 21.2% in group 2, p<0.001; PWS was 4.7% vs. 11.0% in group 2, p<0.001. Discussions: Radiographic pincer-type findings were common in an asymptomatic population and their prevalence was dependent upon a patient's age, indicating a diagnosis using radiographic parameters should also take into account a patient's age.